Analysis of the Influence of Product Quality, Price, and Brand Image on Repurchaseintention with Customer Satisfaction as Intervening Variables on Customers of Skincare MS Glow Products (Study of the Communities in North Labuhanbatu Regency) - Gisela Nilasari; Paham Ginting; Arlina Nurbaity Lubis (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This objective of the research is to analyze the effect of product quality, price, and brand image variables on repurchase intention with customer satisfaction as an intervening variable on MS Glow skincare products (study of the community in North Labuhanbatu Regency). The research uses quantitative approach. This is an associative research with primaryand secondary data whichare obtained through documentation study and statements list and use Likert scale as the measurement. The sample in this researchis people in North Labuhanbatu Regency with minimum age of 18 years old, and has been a customers who has purchased MS Glow skincare products at least 1 time, the number of respondents is 170 people. The data are collected by distributing questionnaires with accidental sampling technique. The data analysis techniqueuses descriptive statistical analysis and path analysis, using Smart PLS. The research results  found that product quality and brand image directly has a positive and significant effect on customer satisfaction, price has a positive but not significant effect on customer satisfaction. Product quality and price variables directly has a positive and significant effect on repurchase intention, brand image has a positive but not significant effect on repurchase intention. The variable of customer satisfaction has a positive and significant effect on repurchase intention,then indirectly product quality and brand image through customer satisfaction has a positive and significant effect on repurchase intention, price through customer satisfaction has a positive but not significant effect on repurchase intention.